THE EFFECTS OF HANDWASHING HABITS ON HEALTH PROTOCOLS ON SKIN HYDRATION LEVELS AND INCIDENCE OF IRRITANT CONTACT DERMATITIS - Sustiawati _; Indri Hapsari; Irsalina Nurul Putri (Jurnal Farmasi Sains dan Praktis, 2021)
Background: Handwashing using soap or hand sanitizer is one of the health protocols that must be implemented by society to prevent the spreading of SARS-COV2 virus which can cause pneumonia, acute respiratory syndrome and death. The implementation of health protocols during the COVID-19 pandemic caused the habit of handwashing increase. Hence, it can lead to cause irritant contact dermatitis and dry hand skin due to frequent contact with soap or hand sanitizers. Method: This study is an observational study with the sample from the villager of Banyumas regency. The data collection was taken by cluster random sampling and accidental sampling. Results: Considering the health protocol, most of the villager used to wash their hands regularly and 3 respondents (3.00%) of them did not. 100 respondents took the data and 19 respondents (19.00%) have irritant contact dermatitis and the rest did not. Furthermore, for skin hydration levels with dehydration category (0% - 29%) are 50 respondents (50.00%), normal category (30% - 50%) are 38 respondents (38.00%) and hydration category (51% - 100 %) are 12 respondents (12.00%). Chi-Square analysis showed that there was no significant relationship between handwashing habit and the incidence of irritant contact dermatitis with the value of “P” is 0.394> 0.05 and there was a significant relationship between hand washing habits and skin hydration levels with the value of “P” is 0.010 <0, 05. Conclusion: Handwashing habits have a significant relationship to skin hydration levels.